NEEDS TO LOVE AND HAVE MAIN CHARACTER HUMANISTIC STUDY IN THE NOVEL SCARS AND OTHERS BEAUTIFUL THINGS - Risa Alfina Aulinia (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Psychological science that discusses the human needs in his life has become sub-interdisciplinary in literary studies, which is contained in the discussion of humanistic psychology. Maslow, a well-known figure in the study, published his third book Mahzab. In the study, human needs are divided into five and one of them needs love and have. In this discussion the need for love and having a much needed on victims of sexual violence. His struggle to get all the love lost is not easy. The main character goes through a lot of time and self-problems in order to get a normal life and all his loved ones back. This stage of the main character after becoming a victim in order to get his love back is by (1)Being alone wherever he is (2)Always blame himself (3)Go to the psychiatrist (4)Start ventured to believe in people (5)Finding all the love that was lost (6)Realizing mistakes and starting a new life. Keywords: Humanistic psychology, love and have, depression, conscious